The Recent Advances in the Function and Mechanism of Caveolin-1 in Retinal Neovascularization - Zhang, Rui; Dang, Yalong (Current Drug Targets, 2024)
Retinal neovascularization diseases have relatively high rates of evitable blindness. Abnormal retinal neovascularization is their main hallmark, which can damage the structure and function of the eye and lead to impaired vision. Caveolin-1 is a membrane protein that is expressed in many types of retinal cells and is involved in retinal neovascularization. This review presents a comprehensive analysis of global research on specific functions of caveolin-1 in retinal neovascularization. We believe that the mechanism of action of caveolin-1 might be related to the regulation of relevant signal pathways and looked ahead the application prospects of modulating caveolin- 1 in retinal neovascularization diseases.
Keywords: Neovascularization